Decision Support System Terms of Credit Loans using Analytical Hierarchy Process Method (AHP) (Study Case: LPD Temesi Village) - Dewa Ayu Putri Wulandari; Agus Anwar Eka Wahyudi; I Wayan Rinas (International Journal of Engineering and Emerging Technology, 2017)
the credit distribution is one of product of crediting of foundation that very helping for the citizens in increasing the economic. Credit matter foundation is one of institution citizen in which focusing economic field villagers that have functions shelter and help people of village dealing the financial. Being the institution of credit matter in villages the citizen can propose or ask loan credit of money with keep showing some criterion that as way in requirement of propose the credit. To make easier selective process and to achieve the result of objective score so it is needed a supporting system in taking decision where it can help to take decision. The steps of analytical hierarchy process (AHP) namely the making of matrix comparison couple criteria by using scale of AHP, determine comparison matrix, determine the value Eigen vector, determine the maximum of Eigen score, determine the consistence index score and ratio, and doing the normalization the value of score Eigen vector. The next, the heavy of score analytical hierarchy process will be timed with the heavy that having given by the taker decision, where the final score is total value that determining who is the candidate of customer who have rightful authority receiving the loan credit.